FE modelling of the flexural behaviour of square and rectangular steel tubes filled with normal and high strength concrete - Javed, M.F.; Sulong, N.H.R.; Memon, S.A.; Rehman, S.K.U.; Khan, N.B. (Elsevier, 2017)
In this research, numerical investigations were carried out to study the behaviour of concrete filled steel tubes having square or rectangular cross-sections. Separate models were used for both normal strength concrete and high strength concrete. More than 50 experimental results were used to verify the FE model and it was found that the FE model accurately predicts the load-deflection curve and ultimate moment capacity of the Concrete filled steel tube (CFST) beams. Thereafter, a parametric study was carried out to evaluate the effect of depth-to-thickness ratio (20−200), compressive strength of infilled concrete (2–100 MPa), shear span-to-depth ratio (1–8), depth-to-width ratio (0.6–2), and yield strength of steel tube (380–490 MPa) on the flexural behaviour of square and rectangular CFST members. It was found that the depth-to-thickness ratio, yield strength of steel and height-to-width ratio has significant effect on the ultimate capacity of CFST beams. The effect of shear span-to-depth ratio and strength of infilled concrete was found to be marginal. Finally, the results of parametric study and experimental data available in literature were used to check the accuracy of the existing design methods presented in EC4 (2004), CIDECT, AISC (2010) and GB50936 (2014). From comparison, it was found that GB50936 (2014) was more accurate but unsafe for low strength infilled concrete. For all cases, EC 4 (2004) was found to be safe and hence is recommended.